Phase I/II study of adding intraperitoneal paclitaxel in patients with pancreatic cancer and peritoneal metastasis. Issue 13 (7th July 2020) - Yamada, S.; Fujii, T.; Yamamoto, T.; Takami, H.; Yoshioka, I.; Yamaki, S.; Sonohara, F.; Shibuya, K.; Motoi, F.; Hirano, S.; Murakami, Y.; Inoue, H.; et al.
Abstract : Background: Intraperitoneal chemotherapy using paclitaxel is considered an experimental approach for treating peritoneal carcinomatosis. This study aimed to determine the recommended dose, and to evaluate the clinical efficacy and safety, of the combination of intravenous gemcitabine, intravenous nab‐paclitaxel and intraperitoneal paclitaxel in patients with pancreatic cancer and peritoneal metastasis. Methods: The frequencies of dose‐limiting toxicities were evaluated, and the recommended dose was determined in phase I. The primary endpoint of the phase II analysis was overall survival rate at 1 year. Secondary endpoints were antitumour effects, symptom‐relieving effects, safety and overall survival. Results: The recommended doses of intravenous gemcitabine, intravenous nab‐paclitaxel and intraperitoneal paclitaxel were 800, 75 and 20 mg/m 2 respectively. Among 46 patients enrolled in phase II, the median time to treatment failure was 6·0 (range 0–22·6) months. The response and disease control rates were 21 of 43 and 41 of 43 respectively. Ascites disappeared in 12 of 30 patients, and cytology became negative in 18 of 46. The median survival time was 14·5 months, and the 1‐year overall survival rate was 61 per cent. Conversion surgery was performed in eight of 46 patients, and those who underwent resection survived significantly longer than those who were not treated surgically (median survival not reached versus 12·4 months). Grade 3–4 haematological toxicities developed in 35 of 46 patients, whereas non‐haematological adverse events occurred in seven patients. Conclusion: Adding intraperitoneal paclitaxel had clinical efficacy with acceptable tolerability. Abstract : This multicentre phase I/II study was undertaken to determine the recommended dose of the combination of intravenous gemcitabine, intravenous nab‐paclitaxel and intraperitoneal paclitaxel in patients with pancreatic ductal adenocarcinoma and peritoneal metastasis, and to evaluate its clinical efficacy and safety. This regimen exhibited promising clinical efficacy, with acceptable tolerability. Effective and safe in pancreatic cancer Abstract : Antecedentes: La quimioterapia intraperitoneal con paclitaxel se considera una terapia experimental para el tratamiento de la carcinomatosis peritoneal. Este estudio tuvo como objetivo determinar la dosis recomendada y evaluar la eficacia clínica y la seguridad de la combinación de gemcitabina intravenosa, nab‐paclitaxel intravenoso y paclitaxel intraperitoneal en pacientes con cáncer de páncreas y metástasis peritoneales. Métodos: Se evaluaron las frecuencias de las toxicidades limitantes de la dosis, y la dosis recomendada se determinó en la fase I. El objetivo principal de la fase II fue la tasa de supervivencia global a 1 año. Los objetivos secundarios fueron los efectos antitumorales, los efectos de alivio de los síntomas, la seguridad y la supervivencia global. Resultados: Las dosis recomendadas de gemcitabina intravenosa, nab‐paclitaxel intravenoso y paclitaxel intraperitoneal fueron de 800, 75 y 20 mg/m 2, respectivamente. De los 46 pacientes incluidos en la fase II del estudio, la mediana de tiempo hasta el fracaso del tratamiento fue de 6, 0 meses (rango, 0‐22, 6). Las tasas de respuesta y de control de la enfermedad fueron del 45% y 95%, respectivamente. La ascitis desapareció en el 40% de los pacientes, y la citología se negativizó en el 39% de los pacientes. La mediana del tiempo de supervivencia fue de 14, 5 meses y la tasa de supervivencia global a 1 año del 60, 9%. La cirugía de rescate se realizó en ocho (17%) pacientes, y los que se sometieron a cirugía sobrevivieron significativamente más tiempo que los que no fueron tratados quirúrgicamente (mediana de supervivencia no alcanzada versus 12, 4 meses). Las toxicidades hematológicas de grado 3/4 ocurrieron en el 76% de los pacientes, mientras que los eventos adversos no hematológicos se presentaron en el 15% de los pacientes. Conclusión: Agregar paclitaxel intraperitoneal tuvo eficacia clínica con una tolerabilidad aceptable. (UMIN000018878)